Uji Fitokimia Senyawa Metabolit Sekunder Dalam Ekstrak Metanol Bunga Turi Merah (Sesbania grandiflora L. Pers) - Anjar Purba Asmara (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
A beginning investigation about the presence of secondary metabolite compounds in the methanol extract of red grandiflora flower (Sesbania grandiflora L. Pers) has been conducted. The flower which traditionally used as antihyperglycemic therapy has been extracted through methanolic-maceration. The crude extract was phytochemically analyzed by qualitative approach with specific reagent for the each type of the compound. The analysis of functional group prediction is also performed by using FTIR spectrometer. Phytochemical test showed that it contains alkaloid, tannin, polyphenol, flavonoid, quinone, and triterpenoid. The IR spectrum showed that the typical functional group of the secondary metabolite consist of hydroxide (–OH), olefin (C=C), and aromatic which as constituents of phenolic group